2012
DOI: 10.4103/0976-9668.101878
|View full text |Cite
|
Sign up to set email alerts
|

Mirror neurons: Enigma of the metaphysical modular brain

Abstract: Mirror neurons are one of the most important discoveries in the last decade of neuroscience. These are a variety of visuospatial neurons which indicate fundamentally about human social interaction. Essentially, mirror neurons respond to actions that we observe in others. The interesting part is that mirror neurons fire in the same way when we actually recreate that action ourselves. Apart from imitation, they are responsible for myriad of other sophisticated human behavior and thought processes. Defects in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 31 publications
(26 reference statements)
0
38
0
6
Order By: Relevance
“…Based on neurological theory, which explains the relationships between body, mind, and environment, quantitative resemblance is based on the possibility that brain stimulation enhanced the neural drive of group members. Such fact is supported by the Hebbian theory in which simultaneous activation of cells leads to pronounced increases in synaptic strength between those cells 15 . As a consequence, this restructuring could have resulted in enhanced interpretation of the stimuli that people with autism had to process.…”
mentioning
confidence: 48%
See 2 more Smart Citations
“…Based on neurological theory, which explains the relationships between body, mind, and environment, quantitative resemblance is based on the possibility that brain stimulation enhanced the neural drive of group members. Such fact is supported by the Hebbian theory in which simultaneous activation of cells leads to pronounced increases in synaptic strength between those cells 15 . As a consequence, this restructuring could have resulted in enhanced interpretation of the stimuli that people with autism had to process.…”
mentioning
confidence: 48%
“…Moreover, Molnar-Szakacs et al 6 described neuroimaging studies that investigated the imitation of emotional facial expressions, and showed that children with autism have virtually no activity in mirror neurons compared with children in the control group. However, studies with functional magnetic resonance imaging ( fMRI) suggest that a much larger network of brain areas show mirror properties in humans than previously thought 15 . The results presented suggest that the mirror neurons of these individuals are present in the cortical area measured, and are reactive to emotional processing situations.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…This may suggest that empathy is hard-wired in the brain as action observation automatically triggers empathetic processes. Indeed, it has been shown that people who are more empathic have stronger activations of the putative mirror system for hand actions and also the mirror system for emotions, supporting the notion that the MNS is linked to empathy (Acharya et al , 2012, Zaki et al , 2012.…”
Section: A Role In Empathymentioning
confidence: 69%
“…The second abnormality is represented by sensory-motor defects such as temper tantrums, head banging and some stereotyped movements. All these deficiencies and defects are currently considered to be secondary to the abnormal development of mirror neurons (Acharya & Shukla, 2012).…”
Section: Empathy and Autism Spectrum Disordersmentioning
confidence: 99%